Specific knockdown of WNT8b expression protects against phosphate‐induced calcification in vascular smooth muscle cells by inhibiting the Wnt–β‐catenin signaling pathway. Issue 4 (21st November 2018) - Tian, Bin‐Yao; Yao, Li; Sheng, Zi‐Tong; Wan, Peng‐Zhi; Qiu, Xiao‐Bo; Wang, Jian; Xu, Tian‐Hua
Abstract : In the last 10 years, the prevalence, significance, and regulatory mechanisms of vascular calcification (VC) have gained increasing recognition. The aim of this study is to explore the action of WNT8b in the development of phosphate‐induced VC through its effect on vascular smooth muscle cells (VSMCs) in vitro by inactivating the Wnt–β‐catenin signaling pathway. To explore the effect of WNT8b on the Wnt–β‐catenin signaling pathway and VC in vitro, β‐glycerophosphate (GP)‐induced T/G HA‐VSMCs were treated with small interfering RNA against WNT8b (Si‐ WNT8b ), Wnt‐β‐catenin signaling pathway activator (LiCl) and both, respectively. Reverse transcription quantitative polymerase chain reaction and western blot analysis were used to determine the messenger RNA and protein levels of WNT8b, α‐smooth muscle actin (α‐SMA), calcification‐associated molecules, and molecules related to the Wnt signaling pathway. The TOP/FOP‐Flash reporter assay was performed to detect the transcription activity mediated by β‐catenin. Si‐ WNT8b reduced calcium deposition and the activity of alkaline phosphatase (ALP), increased the α‐SMA level, and decreased bone morphogenetic protein 2, Pit1, MSX2, and Runt‐related transcription factor 2 levels, whereas stimulation of LiCl worsened β‐GP‐induced calcium deposition, increased the activity of ALP, and reduced the α‐SMA expression level. Si‐ WNT8b reduced the levels of WNT8b, frizzled‐4, β‐catenin, phospho‐GSK‐3β (p‐GSK‐3β), and cyclin‐D, whereas it increased the levels of p‐β‐catenin and GSK‐3β, indicating that si‐ WNT8b could alter the Wnt–β‐catenin signaling pathway and thus hamper the VC in T/G HA‐VSMC, which was further demonstrated by the TOP/FOP‐Flash assay and detection of the β‐catenin expression level in the nucleus. Altogether, we conclude that WNT8b knockdown terminates phosphate‐induced VC in VSMCs by inhibiting the Wnt–β‐catenin signaling pathway. Abstract : WNT8b knockdown terminates phosphate‐induced vascular calcification in vascular smooth muscle cells by inhibiting the Wnt–β‐catenin signaling pathway.